O wpływie poziomu obciążenia i wzmocnienia naprężonymi taśmami CFRP na nośność i odkształcalność belek żelbetowych - Kotynia, Renata; Lasek, Krzysztof; Staśkiewicz, Michał (Wydawnictwo Politechniki Łódzkiej, 2011)
Praca dotyczy wzmacniania żelbetowych belek na zginanie przy użyciu naprężonych taśm kompozytowych CFRP. Przedstawiono program i wyniki własnych badań doświadczalnych belek wzmacnianych pod obciążeniem. Przeprowadzono analizę wpływu poziomu obciążenia belek przed wzmocnieniem na ich nośność i odkształcalność.

Paper describes experimental research of reinforced concrete beams strengthened for flexure with pretension CFRP laminates. Before strengthening beams were exhausted to 25% or 75% of load capacity of non-strengthened beam. Research showed high efficiency of strengthening with pretension strips. Strengthening ratio varied in the range from 1,9 to 2,2 of the non-strengthened beam. Flexural strengthening of RC beams with pretension CFRP strips is very effective both for ultimate limit state and serviceability limit state, especially in case of highly exhausted elements before strengthening. Using of the active strengthening system causes significant reduction of strains in concrete and mid-span deflections and increase in stiffness of tested elements.
About the preloading and strengthening level with pretension CFRP strips on load capacity and ductility of reinforced concrete beams